2012
DOI: 10.1016/b978-0-12-394622-5.00003-1
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Hedgehog Signaling

Abstract: The notion of noncanonical hedgehog (Hh) signaling in mammals has started to receive support from numerous observations. By noncanonical, we refer to all those cellular and tissue responses to any of the Hh isoforms that are independent of transcriptional changes mediated by the Gli family of transcription factors. In this chapter, we discuss the most recent findings that suggest that Patched1 can regulate cell proliferation and apoptosis independently of Smoothened (Smo) and Gli and the reports that Smo modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
151
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(157 citation statements)
references
References 67 publications
5
151
0
1
Order By: Relevance
“…Recent analysis of the cis-regulatory modules of HH-regulated genes has revealed that cells interpret the levels of HH signaling through differential affinity GLI-binding sites in target genes, whereas tissue specificity is achieved through the participation of co-activators (Balaskas et al, 2012;Oosterveen et al, 2012Oosterveen et al, , 2013. Although the required receptors PTCH1/PTCH2 and SMO are committed to propagating canonical HH signaling, in some processes pathway activation does not result in GLI-induced transcriptional changes and this is referred to as non-canonical HH signaling (Brennan et al, 2012;Briscoe and Therond, 2013;Jenkins, 2009) (see Box 1).…”
Section: The Hh Signaling Pathway In Mammalsmentioning
confidence: 99%
“…Recent analysis of the cis-regulatory modules of HH-regulated genes has revealed that cells interpret the levels of HH signaling through differential affinity GLI-binding sites in target genes, whereas tissue specificity is achieved through the participation of co-activators (Balaskas et al, 2012;Oosterveen et al, 2012Oosterveen et al, , 2013. Although the required receptors PTCH1/PTCH2 and SMO are committed to propagating canonical HH signaling, in some processes pathway activation does not result in GLI-induced transcriptional changes and this is referred to as non-canonical HH signaling (Brennan et al, 2012;Briscoe and Therond, 2013;Jenkins, 2009) (see Box 1).…”
Section: The Hh Signaling Pathway In Mammalsmentioning
confidence: 99%
“…The definition of “non-canonical Shh signaling” refers to the cellular responses to Shh ligand that are independent of the activation of the Gli family of transcription factors. At least two separate non-canonical Shh signaling pathways are characterized: one is through Ptch1 but is unrelated to its inhibition on Smo; another is through Smo but is beyond Gli regulation (Figure 1C) (Brennan et al, 2012). …”
Section: Sonic Hedgehog Signaling: Components Routes and Mechanismmentioning
confidence: 99%
“…Indeed, in the absence of Shh ligand, Ptc1 overexpression induces apoptosis both ex vivo and in vitro, an effect that is not suppressed by Smo overexpression. In support of this model, Ptc has been shown to interact physically with the adaptor protein DRAL (Fhl2), which in turn recruits one of the caspase recruitment (CARD)-domain containing proteins TUCAN (Card8) or NALP1 (NLR family, pyrin domain containing 1; Nlrp1), as well as caspase 9, thereby activating caspase 9-dependent apoptosis (Brennan et al, 2012).…”
Section: Non-canonical Hh Signallingmentioning
confidence: 99%
“…The most extensively studied of these is the proposed role of Ptc as a dependence receptor (Brennan et al, 2012). According to these analyses, the activity of Shh as a survival factor is mediated by opposing the apoptosis-promoting activity of Ptc.…”
Section: Non-canonical Hh Signallingmentioning
confidence: 99%
See 1 more Smart Citation